Production And Characterization Of Electrical Conductive Polymeric Hybrid Composites Containing Organic And Inorganic Materials - Sever, Kutlay; Yılmaz, Hüseyin; Atagur, Metehan; Şen, İbrahim (International Journal of Computational and Experimental Science and Engineering, 2025)
Polymer composites are becoming more and more involved in many industries such as aerospace, automotive, transportation and sports. As usage increases in the commercial market, the polymer industry provides materials to almost every area of technology and industry, allowing the production of materials or new materials to be produced and the development or orientation of new types of needs. In the last 10 years, the use of polymer composites has become the new materials needed in electronic technology. The aim of this study is to investigate the effects of polypropylene (PP) on mechanical and conductivity properties by using mica (M) as an inorganic filler and carbon nano tube (CNT) as an organic filler. Before hybrid composite materials were produced, polypropylene (PP) and M-PP composites were produced and composite with the best mechanical properties were selected. PP-M composites were produced by using a thermokincetic mixer with the addition of mica in 10%, 20%, and 30% weight ratios. Hybrid composites were manufactured using CNT addition into PP-20M with %1, %3, %5, and %7 weight ratios. Mechanical properties of the composite materials produced using tensile and bending tests and viscoelastic properties by dynamic mechanical analysis (DMA), thermal properties by differential scanning calorimeter (DSC) and thermogravimetric (TGA) analyses and morphological structures by scanning electron microscopy (SEM) were investigated